Enhancing the Students' Reading Comprehension with Tri-Focus Steve Snyder Techniques - Suwarni, Andi; Yany, Muhammad (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This research sought to elucidate how students' reading comprehension can be enhanced by identifying main ideas and sequencing details. To elucidate this enhancement, the researcher employed a classroom action research (CAR) method, which was executed across two cycles, each comprising four meetings. The setting for this research was the eighth-grade cohort at SMP Negeri 6 Watampone, comprising 39 participants. Data collection employed comprehension tests and systematic observations of student engagement. Analysis involved quantitative calculation of mean scores and improvement percentages between cycles. Qualitative observation data complemented the quantitative findings, providing a comprehensive assessment of the technique's impact on reading performance. One search outcome demonstrated that the implementation of the sustained silent reading method by using tri-Steve Sniderstechniqyieldede yielthe the ded an Steve Nisonimprovement in the students' recomprehension, specifically about literacy understanding, as substantiated by the mean score of the first cycle, which was recorded at 62.75, categorized as fair, and ranged from 76 to 76from8, which is classified as good in the second cycle. Consequently, an enhancement in students' reading comprehension abilities was achieved through an increase in their ability to identify and sequence, including. The Tri-Focus Steve Snyder approach constitutes one of the pedagogical strategies for teaching reading comprehension that has the potential to enhance the literal comprehension skills of the eighth-grade students at SMP Negeri 6 Watampone.